Pengaruh Penerapan Modernisasi Administrasi Perpajakan dalam Struktur Organisasi dan E-System Terhadap Tingkat Kepatuhan WPOP (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Jakarta Kembangan) - Riaty Handayani; Syifa Nur Rahmawati (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2018)
To optimize state’s revenues, the government made tax reforms more comprehensively. One of them is administrative reform which is implemented through modernization program of tax administration. The purpose this study to determine the application of administrative modernization consisting of organizational restructuring, and E-System and its influence on compliance of Individual Taxpayers in Tax Service Pratama Kembangan Jakarta. This research belongs to the type of causal research, that is research which aims to test the hypothesis about the influence of one or several variables on other variables ie independent variable (modernization of organizational structure and E-System) to the dependent variable (WPOP Compliance). The result of the research shows variables organizational structure and E-system have a significant effect on individual taxpayer compliance in the Tax Office (KPP) Pratama Jakarta Kembangan.